Arrangement and Implementation of Tri Hita Karana and Sad Kerthi in Awig-Awig Subak Anggabaya (Penatih Village, East Denpasar District, Denpasar City) - Parayusa, Anak Agung Bagus Willy Pradnya; Ibrahim, Ibrahim; Arjawa, A. A Gede Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Tri Hita Karana (THK) is a philosophy, where if we want to live happily, then we must build harmony with God Almighty, as the Creator of the universe (Parhyangan), build harmony with others (Pawongan), and build harmony with nature. (Paringan). Presumably, all human beings want happiness and live in harmony. Apart from the Tri Hita Karana concept, currently the Sad Kerthi concept is being popular among Balinese people. The concept of Sad Kerthi is very interesting to study. Especially if the study is carried out in the Subak system. It's interesting because Subak is an ancestral heritage that still exists today in modern society. A study of Sad Kerthi on Subak will show the extent to which Subak is able to implement Sad Kerthi. On the other hand, it is also true how big the influence of the Sad Kerthi concept is in efforts to stabilize Subak. So the study carried out will show Subak's resilience which is backed up with local wisdom. Thus, the formulation of the problem in this research is how the Tri Tri Hita Karana and Sad Kerthi are regulated in the awig-awig Subak Anggabaya, and how is the implementation of the Tri Hita Karana and Sad Kerthi regulated in the awig-awig Subak Anggabaya. The type of research in this scientific writing is empirical legal research, namely research using field data as the main data source, such as the results of interviews and observations. The approach that the author uses in this research is a legal sociology approach. The legal sociology approach is an approach that analyzes how reactions and interactions occur when the norm system works in society with data sources, namely primary and secondary data. The arrangement of Tri Hita Karana in awig-awig Subak Anggabaya is reflected in the elements of Tri Hita Karana, namely the parhyangan aspect, the pawongan aspect and the palemahan aspect. The provisions of the articles in the awig-awig Subak Anggabaya regulate these three aspects. Meanwhile, the Sad Kerthi arrangements consisting of atma kerthi, ocean kerthi, wana kerthi, dhanu kerthi, jana kerthi, jagat kerthi are not fully regulated. Overall, the implementation of Tri Hita Karana at awig-awig Subak Anggabaya went well. Although there are several norms whose implementation has been modified and do not work.